If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -1184 = 7x + -1976 Reorder the terms: -1184 + 12x = 7x + -1976 Reorder the terms: -1184 + 12x = -1976 + 7x Solving -1184 + 12x = -1976 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1184 + 12x + -7x = -1976 + 7x + -7x Combine like terms: 12x + -7x = 5x -1184 + 5x = -1976 + 7x + -7x Combine like terms: 7x + -7x = 0 -1184 + 5x = -1976 + 0 -1184 + 5x = -1976 Add '1184' to each side of the equation. -1184 + 1184 + 5x = -1976 + 1184 Combine like terms: -1184 + 1184 = 0 0 + 5x = -1976 + 1184 5x = -1976 + 1184 Combine like terms: -1976 + 1184 = -792 5x = -792 Divide each side by '5'. x = -158.4 Simplifying x = -158.4
| x/12-3=3 | | 3(5x+2)=39 | | x/13+12=19 | | f(x)=x^2-10x+1 | | 2a(5a-13)=47 | | H=16x^2+112t+960 | | 5-5.2x=1-2.8x | | 3x+6(0)=12 | | 2p+2+p=-29 | | 3(x-3)+2=5 | | 10-y=-24-4x | | 19w-20w+-20=-9 | | x/12-5=6 | | 8(t+2)-3(2-4)=6(t-7)+8 | | 3r^6-11r^5-20r^4=0 | | 3x-2+12=x+10 | | 0.50x+0.25(50)=21.5 | | 3(0)+6y=12 | | x-36=3(28-x) | | x(40.00+15.25+9.50)=213.25 | | -4(b-6)=-7(b+6)+3b | | X^2-2-14=0 | | 7x+5=6-(6x-6) | | 3-4x+6x=-21 | | 16x^2-24m+9=0 | | Y=-2.5x^2+10x+8 | | 8-7x-6x=8 | | 6-xw=vw+1 | | X-(1+3(3))2=17 | | 2x^5+x^4-2x-1=0 | | (x)(y)=20 | | y=0.04x |